2022
DOI: 10.3389/fpsyg.2022.898405
|View full text |Cite
|
Sign up to set email alerts
|

The Depleting and Buffering Effects of Telecommuting on Wellbeing: Evidence From China During COVID-19

Abstract: Meta-analytical research has demonstrated the benefits brought by telecommuting to wellbeing. However, we argue that such a setup in the course of the coronavirus disease pandemic exerts negative effects. On the basis of conservation of resources theory, this study determined how telecommuting depletes wellbeing (defined by job satisfaction and emotional exhaustion) through obstructing psychological detachment from work. Moreover, we incorporated family interfering with work and family–work enrichment as moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…In the case of teleworking, the literature shows mixed results. As the level of telecommuting increases, leading to minimal psychological separation from work, it can reduce well-being [40]. Some researchers, however, did not find a significant effect of teleworking on job satisfaction, but found that the effect on work-life balance was usually negative [41].…”
Section: Flexible Work Arrangementsmentioning
confidence: 99%
“…In the case of teleworking, the literature shows mixed results. As the level of telecommuting increases, leading to minimal psychological separation from work, it can reduce well-being [40]. Some researchers, however, did not find a significant effect of teleworking on job satisfaction, but found that the effect on work-life balance was usually negative [41].…”
Section: Flexible Work Arrangementsmentioning
confidence: 99%
“…Golden also found that teleworking has a positive association with organizational commitment and a negative one with turnover intentions; however, this relationship is mediated by work exhaustion [ 139 ]. On the other hand, teleworkers can feel some degrees of psychological detachment from work, which negatively influences well-being (measured by job satisfaction and emotional exhaustion); however, its impact can be reduced by family interfering with work [ 140 ]. Teleworking also has some impact on the mental and physical health of employees.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent use of non-office equipment, including chairs without armrests or laptops with no external monitor, exacerbates neck, shoulder, and lower back pain among telecommuters [ 39 , 40 ]. Additionally, during the transition to remote work, telecommuters may lose resources at work, such as coworkers’ support, resulting in social isolation [ 41 ]. Many studies have suggested that social isolation and lack of support from coworkers lead to health impairments and are predictive of depressive disorders and burnout [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%